COMMUNITY HEALTH CENTER READINESS FOR THE PROVISION OF TUBERCULOSIS SERVICES IN INDONESIA - Suparmi; Harimat Hendarwan; Ika Saptarini; Pandji Wibawa Dhewantara; Raflizar; Amir Suudi; Rosita; Oktarina; Yuyun Yuniar (Universitas Airlangga, 2026)
Background: Indonesia has the second-highest Tuberculosis (TB) cases globally and contributes to 45% of newly diagnosed TB cases, combined with India. The successful interventions for TB control depend largely on general health systems, including the availability and readiness of TB services at primary health care facilities. Aims: This study assessed Community Health Centers (CHCs) readiness for TB services in Indonesia. Methods: Data from Indonesian Health Facility Research (RIFASKES) conducted in 2019 were used for the analysis, which included 9,831 CHCs. Readiness for TB services was evaluated using the World Health Organization (WHO) Service Availability and Readiness Assessment (SARA) tool and categorized into three domains contributing to overall health facility readiness. Results: Overall, readiness to provide TB services was 29.7%. The diagnostic domain had the lowest readiness (17.1%), followed by the medicine domain (34.0%), whereas the staff and training domains demonstrated the highest readiness (37.9%). Geographically, health center readiness varied by province, ranging from 18.6% in Papua to 44.6% in Yogyakarta. Conclusion: The readiness of CHCs to provide TB services remains low. Therefore, the government needs to increase investment and ensure equitable distribution of facilities at CHCs to strengthen TB service implementation and accelerate TB elimination in Indonesia. Keywords: community health center, health facility, readiness, tuberculosis